Estimation of Excitation Capacitance Requirement of an Isolated Multi-phase Induction Generator for Power Generation - Alok Kumar Mohanty; K B Yadav (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
Self Excited induction generators are used in remote places for electrical power generation from both conventional as well as non-conventional sources. An Induction generator can operate as a capacitor excited machine provided the machine is driven beyond synchronous speed and a suitable capacitor is connected across its terminals. In this paper a technique has been proposed to estimate the values of excitation capacitances to maintain desired terminal voltages in a multi-phase induction generator. A mathematical model using nodal admittance technique of a six-phase induction generator has been analyzed. Genetic algorithm technique is applied here to obtain the unknown parameters and the capacitance requirements to obtain desired terminal voltages under various operating conditions.